Nd:YAG capsulotomy rates after use of the AcrySof acrylic three piece and one piece intraocular lenses. Issue 11 (18th October 2005) - Mian, S I; Fahim, K; Marcovitch, A; Gada, H; Musch, D C; Sugar, A
Abstract : Background/aim: Acrylic lens size and shape may influence the rate of posterior capsule opacification (PCO) and need for Nd:YAG capsulotomy. The aim of this study is to compare the Nd:YAG capsulotomy rate of the three piece acrylic/PMMA AcrySof MA series lens with the one piece acrylic AcrySof SA series lens. Methods: 434 eyes of 329 patients who had cataract extraction and implantation of one of four types of intraocular lenses (IOLs) were evaluated for rate of Nd:YAG capsulotomy. 176 eyes received the acrylic AcrySof MA30AC IOL, 71 eyes the acrylic AcrySof MA60AC IOL, 45 eyes the acrylic AcrySof SA30AL IOL, and 142 eyes the acrylic AcrySof SA60AT IOL. Results: The rates of Nd:YAG capsulotomy with the three piece IOL (MA30AC/MA60AC) and the one piece IOL (SA30AL/SA60AT) were 1.2% and 2.1% at 6 months, 2.8% and 5.9% at 12 months, and 3.6% and 7.5% at 24 months, respectively. The incidence of Nd:YAG capsulotomy was higher in patients who received the one piece IOL (p = 0.01, log rank test). There was no difference in Nd:YAG capsulotomy rates when comparing lens optic size, age, sex, history of pars plana vitrectomy, and diabetes mellitus. Conclusions: This study shows a greater incidence of Nd:YAG capsulotomy in patients who receive one piece acrylic AcrySof lenses when compared to those who receive three piece acrylic AcrySof lenses.